Development of vertical diffusion solar stills utilizing folded sheets technology - Seleem, Amr (AUC Knowledge Fountain, 2016)
Fresh water shortage is now a global problem the world is facing, and solar stills address a sustainable solution towards such crisis. This study entails the importance of desalination, specifically solar distillation. Diffusion stills have been effective in water desalination. This work presents a model of the distillation process using vertical single-effect diffusion stills. In the provided models, two geometry patterns have been utilized: the flat sheets and the folded sheets. This study aims to evaluate the applicability of utilizing folded sheets on the performance of the still using wick and without wick. A semi-analytical model utilizing the flat sheet and the folded sheet have been developed to analyze the diffusion process. Furthermore, a software computer code using Engineering Equation Solver (EES) issued to solve the equations of the developed semi-analytical model. An experimental test rig has been constructed, and used for the validation of the semi-analytical model to find its best range of validity. Also, it is validated against former literature results. A good agreement is reached with feed rates of flow up to 0.0211 kg/m2-s. Moreover, a parametric study for the still utilizing flat sheets model is carried out to assess the performance of the still; it is found that the controllable parameters are:(i) hot plate temperature; (ii) cold plate temperature;(iii) diffusion gap thickness;(iv)feed water temperature; and (v) feed rate of flow; have an impact on the still’s productivity. The most dominant parameters that influence the productivity of the still are the hot plate temperature that ranges from (55- 90 °C), the diffusion gap thickness in range of (5-10 mm), the feed water temperature (20-50 °C), and the feed flow rate in range of (0.00694-0.0211 kg/m2-s). The experimental work utilizing folded-chevron pattern sheets, both with wick and wickless, have been carried out and have been compared to the flat sheets to assess still’s productivity. A comparative analysis has been conducted to evaluate the productivity; it is found that the folded sheet with wick has a higher productivity among other sheets. It indicates the superiority of the wicked folded over the wickless folded and the flat sheet. The folded pattern showed a higher performance by an average increase in the condensate to feed ratio by 27 % through the operating hot plate temperature that ranges from 60 to 90°C.